Quantitative analysis of a wind energy conversion model - Zucker, Florian; Strunz, Andreas; Gräbner, Anna; Meyn, Jan-Peter (European Journal of Physics, 2015)
A rotor of 12 cm diameter is attached to a precision electric motor, used as a generator, to make a model wind turbine. Output power of the generator is measured in a wind tunnel with up to 15 m s-1 air velocity. The maximum power is 3.4 W, the power conversion factor from kinetic to electric energy is cp = 0.15. The v3 power law is confirmed. The model illustrates several technically important features of industrial wind turbines quantitatively.
UnivIS-Import:2015-04-14:Pub.2015.nat.dphy.PI.PDP.quanti
Keywords: Betz factor; demonstration experiment; model; renewable energy; wind energy; wind turbine